Lysosomal storage of oligosaccharide and glycosphingolipid in imino sugar treated cells. - Boomkamp, S; Rountree, J; Neville, D; Dwek, R; Fleet, G; Butters, T (2010)
Sandhoff and Tay-Sachs disease are autosomal recessive GM2 gangliosidoses where a deficiency of lysosomal beta-hexosaminidase results in storage of glycoconjugates. Imino sugar (2-acetamido-1,4-imino-1,2,4-trideoxy-L-arabinitol) inhibition of beta-hexosaminidase in murine RAW264.7 macrophage-like cells led to lysosomal storage of glycoconjugates that were characterised structurally using fluorescence labelling of the free or glycolipid-derived oligosaccharides followed by HPLC and mass spectrometry. Stored glycoconjugates were confirmed as containing non-reducing GlcNAc or GalNAc residues resulting from the incomplete degradation of N-linked glycoprotein oligosaccharide and glycolipids, respectively. When substrate reduction therapeutics N-butyl-deoxynojirimycin (NB-DNJ) or N-butyldeoxygalactonojirimycin (NB-DGJ) were applied to the storage phenotype cells, an increase in glucosylated and galactosylated oligosaccharide species was observed due to endoplasmic reticulum alpha-glucosidases and lysosomal beta-galactosidase inhibition, respectively. Hexosaminidase inhibition triggered a tightly regulated cytokine-mediated inflammatory response that was normalised using imino sugars NB-DNJ and NB-DGJ, which restored the GM2 ganglioside storage burden but failed to reduce the levels of GA2 glycolipid or glycoprotein-derived N-linked oligosaccharides. Using a chemically induced gangliosidosis phenotype that can be modulated with substrate lowering drugs, the critical role of GM2 ganglioside in the progression of inflammatory disease is also demonstrated.